2022
DOI: 10.3390/ani12192714
|View full text |Cite
|
Sign up to set email alerts
|

Urban Birds as Antimicrobial Resistance Sentinels: White Storks Showed Higher Multidrug-Resistant Escherichia coli Levels Than Seagulls in Central Spain

Abstract: The presence of AMR bacteria in the human–animal–environmental interface is a clear example of the One Health medicine. Several studies evidence the presence of resistant bacteria in wildlife, which can be used as a good indicator of anthropization level on the ecosystem. The fast increase in AMR in the environment in the last decade has been led by several factors as globalization and migration. Migratory birds can travel hundreds of kilometers and disseminate pathogens and AMR through different regions or ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
0
12
2
Order By: Relevance
“…In the Iberian Peninsula, white storks commonly rely on landfills as a food source [59] and exhibit altered migration patterns, with many individuals shortening or even stopping migration to Africa. In this sense, it has been suggested that open landfills or wastewater sites could be key for the acquisition and dissemination of AMR among wildlife since they are high-risk environments for the presence of antibiotic residues and antimicrobial-resistant bacteria [3,60,61]. Despite a moderate prevalence in our study and an omnivorous diet with occasional scavenging and presence in landfills, the Corvidae family did not show alarming results concerning AMR.…”
Section: Discussioncontrasting
confidence: 57%
“…In the Iberian Peninsula, white storks commonly rely on landfills as a food source [59] and exhibit altered migration patterns, with many individuals shortening or even stopping migration to Africa. In this sense, it has been suggested that open landfills or wastewater sites could be key for the acquisition and dissemination of AMR among wildlife since they are high-risk environments for the presence of antibiotic residues and antimicrobial-resistant bacteria [3,60,61]. Despite a moderate prevalence in our study and an omnivorous diet with occasional scavenging and presence in landfills, the Corvidae family did not show alarming results concerning AMR.…”
Section: Discussioncontrasting
confidence: 57%
“…Antimicrobial resistance was generally lower in 2023. Gulls, as sentinels for antimicrobial resistance and carriers of Salmonella spp., may offer valuable insights into the environmental impact of measures addressing AMR in human and veterinary medicine [ 33 , 34 , 35 ]. Regulations aiming to control this serious public health problem have been in place since 2006, when the European Union prohibited the use of antibiotics as growth promoters [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A characterisation of resistant bacteria isolated from wild birds showed a variety of antimicrobial resistance patterns, including tetracycline resistance [5,10,[28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%